Strategi Pengelolaan tempat pemrosesan akhir (TPA ) Sampah Batu Canai di Kelurahan Pematang Reba Indragiri Hulu - Amalia Prafitra Harman; Yusni Ikhwan Siregar; Ridwan Manda Putra (Jurnal Zona, 2020)
To solve the waste problem in Indragiri Hulu Regency, the Regency Government built a Landfill (TPA). This waste Landfill (TPA) is located at Jalan Batu Canai, Pematang Reba Village, Rengat Barat District. However, the management of this TPA has experienced various obstacles so that it does not run optimally so it is interesting for further research.This research was conducted in August 2020 at the Batu Canai waste landfill (TPA) using survey methods, literature study and interviews. The type of data used in the form of a combination of quantitative and qualitative research will be described descriptively. The variables of this study include 1.) The existing condition of Batu Canai Waste Landfill (TPA) Pematang Reba Village, 2) The impact of the existence of Batu Canai Final Disposal Site (TPA) of Batu Canai Garbage in Pematang Reba Village on the environment, social and economy according to the perceptions of the community around the TPA , 3) Management strategy of Batu Canai waste landfill  (TPA) Pematang Reba Village. The existing condition of TPA Batu Canai in terms of facilities and infrastructure is quite adequate, although some infrastructure and operational facilities are damaged. From the calculation results, the estimated service life of Batu Canai waste landfill (TPA) is 8 years and 9 months. For the impact of the existence of TPA Batu Canai, according to the community's perception around the TPA, from a socio-economic perspective, their response was positive and from an environmental perspective, their response was negative. Meanwhile, the alternative management strategies for Batu Canai waste landfill were analyzed through SWOT analysis. From the results of the SWOT analysis, it was found that the condition of the TPA was in Quadrant III and the right alternative strategy for managing the Batu Canai Final Processing Site (TPA) in Pematang Reba Village was a WO (Weaknesses-Opportunities) strategy, namely 1) Optimizing the Controlled landfill system, 2) Support Government to establish a special agency for managing TPA, 3) Utilizing good waste processing technology to process organic waste into bio energy, 4) Empowering and fostering communities to establish a Waste Bank.